EKSPLORASI PENGALAMAN GURU DALAM MENGGUNAKAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR - Haryono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore teachers' experiences in using information technology-based learning media in the subject of Natural and Social Sciences (IPAS) at elementary schools. Although the use of technology in education has developed rapidly, challenges in its implementation at the elementary school level, such as limited information technology infrastructure and teachers' digital competence, remain issues that need to be addressed. This study employs a qualitative approach with a case study design conducted at SDN Karangduak II. Data were collected through in-depth interviews and participatory observations, which were then analyzed using thematic analysis. The results show that despite challenges related to limited hardware and internet connectivity issues, the use of information technology in learning media for IPAS provides significant benefits in increasing student engagement and understanding. Teachers reported that information technology helps them explain abstract concepts and present materials in a more interactive manner. Despite some obstacles, teachers have adapted by making use of available devices, such as learning applications and digital media, and collaborating to enhance their digital skills. This study suggests that elementary schools should improve their information technology infrastructure and provide ongoing training for teachers to optimize the use of information technology in teaching and learning. Keywords: Learning Media, Information Technology, Teacher, IPAS, Elementary School